Rethinking security in the age of migration trust and emancipation in Europe - Bilgiç, Ali (Routledge research on the global politics of migration, 2013)
Migration and especially irregular migration are politically sensitive and highly debated issues in the developed world, particularly in Europe. This book analyses irregular protection-seeking migration in Europe, with close attention to sub-Saharan migration into the EU, and emancipatory security theory